Hydrogen Dynamics in Cyanobacteria Dominated Microbial Mats Measured by Novel Combined H2/H2S and H2/O2 Microsensors - Maegaard, Karen; Nielsen, Lars P.; Revsbech, Niels P. (Frontiers in Microbiology, 2017)
Hydrogen may accumulate to micromolar concentrations in cyanobacterial mat communities from various environments, but the governing factors for this accumulation are poorly described. We used newly developed sensors allowing for simultaneous measurement of H2S and H2 or O2 and H2 within the same point to elucidate the interactions between oxygen, sulfate reducing bacteria, and H2 producing microbes. After onset of darkness and subsequent change from oxic to anoxic conditions within the uppermost ∼1 mm of the mat, H2 accumulated to concentrations of up to 40 μmol L-1 in the formerly oxic layer, but with high variability among sites and sampling dates. The immediate onset of H2 production after darkening points to fermentation as the main H2 producing process in this mat. The measured profiles indicate that a gradual disappearance of the H2 peak was mainly due to the activity of sulfate reducing bacteria that invaded the formerly oxic surface layer from below, or persisted in an inactive state in the oxic mat during illumination. The absence of significant H2 consumption in the formerly oxic mat during the first ∼30 min after onset of anoxic conditions indicated absence of active sulfate reducers in this layer during the oxic period. Addition of the methanogenesis inhibitor BES led to increase in H2, indicating that methanogens contributed to the consumption of H2. Both H2 formation and consumption seemed unaffected by the presence/absence of H2S.